THE INFLUENCE OF SELF-EFFICACY, EMPLOYEE BEHAVIOR, AND INTERNAL COMMUNICATION ON ORGANIZATIONAL CULTURE THROUGH THE PERFORMANCE OF THE MINISTRY OF MARINE AFFAIRS AND FISHERIES - Widya Dini, Winda; Madiistriyatno, Harries; Taufiq, Kemal (Jurnal Manajemen Bisnis Dan Organisasi, 2025)
This study aims to analyze the influence of self-efficacy, employee behavior, and internal communication on organizational culture and employee performance at the Ministry of Marine Affairs and Fisheries. In addition, the study also examines the effect of organizational culture on performance. The research population consists of 18,120 employees, with a sample of 100 respondents determined using a probability sampling technique with the simple random sampling method, based on the Slovin formula. Data were collected through questionnaires and observations. This study employed a descriptive quantitative approach, with data analysis conducted using the SmartPLS 3.0 application. The results of the study indicate that self-efficacy, employee behavior, and internal communication have a positive and significant influence on organizational culture. These three variables also show a positive and significant impact on employee performance. Furthermore, organizational culture is proven to have a positive and significant effect on performance. These findings suggest that improvements in self-efficacy, positive employee behavior, and effective internal communication can strengthen organizational culture and directly contribute to enhancing employee performance within the Ministry of Marine Affairs and Fisheries.